The determinants of capital structure: the case of European firms - Silva, Carolina Maria Borges Branco da (2018)
The Capital structure is considered a matter of discussion in the area of corporate finance for many researchers, and the conclusions are not consensual. The present study aims to assess the determinants of capital structure in European companies, identifying the impact of economic and institutional variables on it. This analysis covers 753 European companies for a period of nine years, and the results are in line with the Pecking Order Theory, and suggest that company size, reputation, collateral, business sector and economic context of local and global factors influence the capital structure of companies. It is essential to understand the determinants of capital structure in order to make funding decisions with assertiveness that maximize the goals envisaged by the companies.